Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

In situ formation of chemically integrated and mechanically interlocked interphases enables robust epoxy-copper adhesion - Ting Xin; Zeyu Zheng; Zuo Li; Yue Wu; Yang Liu; Binbin Zhou; Jibao Lu; Xiaoliang Zeng; Fan Yang; Gang Li; Rong Sun; Pengli Zhu (Chemical Engineering Journal, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Regional assessment of multi-pool mangrove carbon across five coastal provinces of China: Heterogeneity, carbon accounting, and contextual screening - Yan Zheng; Wenhai Lu; Chang Liu; Hefeng Wang; Rong Zeng; Yan Xu; Yangyi Ai (Regional Studies in Marine Science, 2026)

Evaluating the effectiveness of marine ecological red lines: an integrated assessment of ecological outcomes and governance performance - Rong Zeng; Wenhai Lu; Chengliang He; Jie Liu; Yan Xu; Chang Liu; Yangyi Ai; Yan Zheng (Frontiers in Marine Science, 2026)
Marine protected areas worldwide often exhibit uneven conservation outcomes, largely due to differences in governance effectiveness and management implementation. As a large-scale spatial conservation policy, Marine Ecological Red Lines (MERLs) have been widely implemented in China to regulate human activities and safeguard critical marine ecosystems. However, their protection effectiveness remains insufficiently evaluated using quantitative and scalable approaches. In this study, we develop an indicator-based assessment framework grounded in the Pressure–State–Response (PSR) model to evaluate the effectiveness of MERLs. The framework integrates indicators of anthropogenic pressures, ecosystem conditions, and management responses, enabling spatially explicit and temporally comparable assessment. We apply this framework to MERLs in Hainan Province over a five-year period (2020–2024) and conduct systematic comparisons with adjacent non-protected areas. Furthermore, correlation analysis is used to examine the relationships between pressure reduction and ecological state changes, providing preliminary insight into the associations between management actions and ecological outcomes. The results show that MERLs are associated with reduced anthropogenic pressures and improved ecological conditions relative to surrounding areas, although spatial heterogeneity in outcomes persists. The proposed framework provides a structured approach for examining interactions among pressures, ecosystem states, and governance responses, and provides quantitative evidence supporting conservation effectiveness assessment at a provincial scale. The proposed framework may also support adaptive management and policy optimization for MERLs and provide practical reference for the implementation of Other Effective Area-Based Conservation Measures (OECMs).

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Spatiotemporal characteristics and influencing factors of phosphorus metabolism in China's food consumption and disposal system - Shenyi Lu; Zheng Guo; Sophia Shuang Chen; Xingchun Cen; Rong Li; Giri Raj Kattel (Journal of Cleaner Production, 2026)

Numerical Simulation of Large Deformation Movement Process of Underwater Slope Subjected to Seismic Loads: A Case Study from the St. Niklausen Landslide - Mingzhe Wei; Zhongde Gu; Ze Rong; Yang Liu; Yang Lu; Defeng Zheng; Tingkai Nian (Journal of Marine Science and Engineering, 2026)
Large deformation runout is a key factor in assessing the hazards posed by underwater landslides. However, conventional kinematic analyses often neglect both the progressive degradation of slope materials and the hydrodynamic response accompanying the interaction between the moving mass and the overlying water. Taking the well-documented St. Niklausen underwater landslide as a representative case, this study employs a coupled Eulerian–Lagrangian (CEL) model to investigate the earthquake-triggered initiation, large deformation movement, and hydrodynamic response of the landslide. A Python 2.7.15-based stress mapping method is developed to establish an accurate initial geostatic stress field for the irregular slope profile. The numerical model reproduces the principal stages of landslide initiation, runout, and deposition. The results reveal a progressive retrogressive failure mechanism in which successive sliding masses interact through a high-strength compression zone. The rear sliding mass continuously transfers compressive work to the frontal mass, thereby maintaining its downslope movement and indirectly promoting basal erosion to a maximum depth of approximately 6.2 m. In addition, rapid landslide motion generates pronounced vortical flow in the overlying water. These flow structures reflect the hydrodynamic response induced by landslide motion, although their net influence on basal resistance and final runout cannot be isolated from the present coupled simulation. These findings clarify the internal mechanical evolution of underwater landslide movement and characterize the accompanying hydrodynamic response, providing a methodological basis for assessing landslide mobility and related underwater hazards.

Strength characteristics, durability, and microstructure properties of GGBS-PG-CCS stabilized dredged marine silt - Yajun Liu; Yang Zheng; Yindong Sun; Ke Wu; Haijun Lu; Gan Cai; Rong Chen (Marine Georesources & Geotechnology, 2026)

Os79, a UDP‐Glycosyltransferase, negatively regulates cadmium tolerance and accumulation in rice - Rui Guo; Hao Yu Wang; Chong Wei Zhong; Rong Rong Ma; Jiu Huang; Jin Chen; Xian Jiao Guan; Lu Zheng; Ren Fang Shen; Ming Qing Liu; Xiao Fang Zhu (Journal of Hazardous Materials, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Profiling hydrophobic organic pollutants in serum from vulnerable populations in Dalian, China - Yubing Dai; Ningbo Geng; Dongying Zheng; Jing Jin; Xianbo Lu; Rong Cao; Haijun Zhang; Jiping Chen (Environmental Pollution, 2026)

A multicomponent Fc-fused subunit vaccine induces cross-protective immunity against porcine reproductive and respiratory syndrome virus QYYZ-like and NADC30-like strains - Linxing Tian; Zhengdan Lin; Mengxi Pan; Yanwen Wen; Mingxing Lu; Shudan Liu; Chao Zhang; Zhenxiang Rong; Jiahui Ma; Ruiqu Zhou; Nan Cao; Xinghua Chen; et al. (Veterinary Microbiology, 2026)

Nanoscale insights into the immobilization of coexisting As(V) and Cd(II) during Fe(II)-driven ferrihydrite transformation - Wei Li; Zhuohao Wu; Yang Lu; Rong Li; Qianying Sun; Zheng Liang; Wencheng Wu; Zhenqing Shi (Chemical Geology, 2026)

ANKFN1 in skin fibroblasts may modulate mast cell activity and is associated with dupilumab response in atopic dermatitis - Qiu-ju Wei; Jia-rong Lu; Wan-yan Xiang; Hai-qi Liang; Si-qi Zhang; Si-yu Huang; Jun-wen Peng; Ze-feng Zhou; Qiu-ju Li; Wen-jun Zheng (Immunologic Research, 2026)

Food sources of the Synaptid Protankyra bidentata and its trophic competition with the sea cucumber Apostichopus japonicus in culture ponds - Jianlong Ge; Teng Lu; Jinjin Wang; Meijie Liao; Xiaojun Rong; Bin Li; Yingeng Wang; Yongxiang Yu; Chunyuan Wang; Zheng Zhang; Zhiqi Zhang (Aquaculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

A novel mechanistic insight into CO2 effects on chain elongation in Clostridium kluyveri based on transcriptomic and ¹³C-targeted metabolomic analyses - Weizhong Huo; Rong Ye; Tong Hu; Yuchao Shao; Zelin Zheng; Ruifu Zhang; Wenjing Lu; Qirong Shen (Water Research, 2026)

Magnesium deficiency limits electron transport efficiency and photosynthesis, and induces oxidative stress in tobacco - Rong-Rong Xie; Jingjuan Gao; Changzheng Wu; Jinping Guo; Qian Cheng; Hailu Wang; Tinmin Liang; Jianjun Lu; Chaoyuan Zheng; Liangquan Wu; Li-Song Chen; Songbiao Chen; et al. (Plant Science, 2026)

Cd(II) adsorption at a biofilm–mineral interface: Capacity penalty, site masking, and behavior shifts induced by bacterial coating - Liangwei Han; Huijie Zheng; Zihao Ding; Yinjie Kang; Jiang Yu; Yineng Lu; Rong Tan; Zhuanjun Zhao (Chemical Engineering Journal, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Seismic mitigation and configuration-based performance study on particle tuned mass damper applied to transmission tower-line system - Kunjie Rong; Junrong Gong; Zheng Lu; Li Tian; Yelei Shen; Mengyao Zhou (Engineering Structures, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Retraction Note: CD142 promotes trophoblast cell migration by inhibiting BCL2-related autophagic degradation of IL-8 - Linmei Zheng; Rong Tang; Lei Shi; Zhongyi Zhou; Jie Song; Zhicheng Lu (In Vitro Cellular & Developmental Biology - Animal, 2025)

Unraveling the effect of sorbitol on Cu-based catalysts for the continuous hydrogenation of CO2-derived ethylene carbonate to methanol and ethylene glycol - Tong-Yang Song; Ji-Zheng Zhang; Jun He; Xian-Lang Chen; Xin-Yuan Huang; Ai-Ping Jia; Xiaohong Li; Rong-Rong Li; Ji-Qing Lu (Chemical Engineering Journal, 2025)

Front margin tectonic deformation characteristics of the Xu–Su arc tectonic belt and its tectonic implications - Rong-ying Zheng; Yun-sheng Yao; Jun Shen; Hao-yuan He; Chun-shan Guo; Xiao-hui Yu; Xun-ye Dai; Lu-wei Li; Xuan-kai Jiao; Zhong-yuan Yu; Zhi-tao Gao (Applied Geophysics, 2025)

Experimental and numerical study on the seismic mitigation performance of particle dampers on transmission tower-line system - Zheng Lu; Yelei Shen; Mengyao Zhou; Kunjie Rong; Li Tian (Soil Dynamics and Earthquake Engineering, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A novel approach to water-salt migration prevention: foamed lightweight soil barrier layer technology - Yang Zhao; Zheng Lu; Jie Liu; Chuxuan Tang; Abdollah Tabaroei; Rong Zhang; Yinuo Feng; Hailin Yao (Cold Regions Science and Technology, 2025)

PtBi nanocatalysts with controlled chain-like structure and composition: Solvothermal synthesis and ethanol oxidation performance - Luo-Yi Yan; Han-Tao Zhang; Xiao-Yu Lu; Li-Ming Liu; Rong-Hua Zhang; Zheng Cheng; Shuai-Wei Fan; Xin-Wen Zhou (Fuel, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Mechanism of pH-sensitive Amphiphilic Endosomal Escape of Ionizable Lipid Nanoparticles for Cytosolic Nucleic Acid Delivery - Zheng-Rong Lu; Da Sun (Pharmaceutical Research, 2025)
Lipid nanoparticles (LNPs) are among the most successful classes of nonviral delivery systems for nucleic acid-based therapeutics in treating human diseases. One of the key challenges in achieving efficient cytosolic delivery of nucleic acids is overcoming endosomal entrapment within cells. Conventional lipid bilayer-forming cationic and amino lipids mediate endosomal escape via the mechanism of lamellar-to-inverted hexagonal phase transition, resulting in suboptimal cytosolic cargo delivery. pH-sensitive amphiphilic cell membrane disruption and endosomal escape have emerged as a strategy for designing protonatable or ionizable lipids, especially nonlamellar lipids, for efficient cytosolic nucleic acid delivery. Nonlamellar amino lipids possess a large wedge-shaped tail structure and do not form stable lipid bilayers. These lipids and their corresponding LNPs remain neutral, non-amphiphilic, or minimally amphiphilic at physiological pH (7.4). They become amphiphilic upon protonation or ionization in acidic endosomes (pH 6.5–5.4). The electrostatic interaction of ionized nonlamellar lipids with the negatively charged endosome membrane, combined with their large wedge-like structures, disrupts the lipid bilayer, facilitating efficient endosomal escape. Additionally, the nonlamellar ionizable lipids can be fine-tuned by altering the structure of amino head groups and lipid tails to achieve the precisely controlled pH-sensitive amphiphilic membrane disruption at endosomal pH. Therefore, these lipids exhibit excellent safety profiles and high efficiency for in vivo delivery of various therapeutic nucleic acids. pH-sensitive amphiphilic membrane disruption and endosomal escape provide a feasible and effective mechanism for designing ionizable lipids for safe and efficient in vivo nucleic acid delivery.

Creep Behavior and Quantitative Prediction of Marine Soft Clay Based on a Nonlinear Elasto-Plastic–Viscous Element Assembly Model - Yajun Liu; Ning Fang; Yang Zheng; Ke Wu; Rong Chen; Haijun Lu; Vu Quoc Vuong (Journal of Marine Science and Engineering, 2025)
Marine soft clay is characterized by a high water content and low strength, exhibiting pronounced creep deformation under long-term loading that threatens the serviceability and durability of coastal infrastructure. Accordingly, this study develops a creep constitutive model that combines elastic, plastic, and viscous effects and quantitatively evaluates time-dependent deformation under varying water contents and stress levels to provide reliable prediction tools for tunnel, excavation, and pile-foundation design. Cyclic creep tests were carried out on reconstituted marine soft clay with water contents of 40–60% and stress ratios of 0.4–1.2 using a pneumatic, fully digital, closed-loop triaxial apparatus. A “nonlinear spring–Bingham slider–dual viscous dashpot in parallel with a standard Kelvin dashpot” element assembly was proposed, and the complete stress–strain relationship was derived. Experimental data were fitted with Python to generate a creep-strain polynomial and verify the model accuracy. The predicted–measured creep difference remained within 10%, and the surface-fit coefficient of determination reached R2 = 0.97, enabling rapid estimation of deformation for the given stress and time conditions. The findings offer an effective method for the precise long-term settlement prediction of marine soft clay and significantly enhance the reliability of the deformation assessments in coastal civil-engineering projects.

Atmospheric nitrogen deposition has minor impacts on the abundance and diversity of arbuscular mycorrhizal fungi and their contribution to soil carbon stock in tropical forests - Andi Li; Peter Meidl; Senhao Wang; Bo Tang; Matthias C. Rillig; Guangcan Yu; Jing Chen; Rongzhen Liu; Zhiyang Lie; Anchi Wu; Lili Rong; Cheng Peng; et al. (Soil Biology and Biochemistry, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

The promotional effect of MoO3 on the CeO2/TiO2 catalyst for simultaneous removal of NO and toluene: From the insights of experimental and DFT studies - Zhuang Hu; Yi-fei Yu; Hai-yuan Zhao; Zheng-long Wu; Rong Guo; Jia-le Zhou; Xin-yue Zhou; Bing Zhang; Yang-wen Wu; Li Zhao; Qiang Lu (Journal of Environmental Chemical Engineering, 2025)

Effect of scenting process on the taste profile of jasmine green tea and the potent bitterness-enhancing compound in jasmine flowers - Jia-Ying Chen; Wen-Wen Luo; Wen-Xuan Li; Ya-Nan Zheng; Xin-Qiang Zheng; Jian-Liang Lu; Yue-Rong Liang; Jian-Hui Ye (Food Research International, 2025)

Nanometabolomics elucidated biological response of 3D printed vascular stents: Towards metabolic reprogramming of metabolome and lipidome - Yu Zeng; Yumeng Liu; Tong Sun; Ge Liang; Luolan Gui; Wen Zheng; Lu Zhang; Yuanping Gao; Yunfei Dang; Rong Fan; Yang Lu; Dingkun Zhang; et al. (Chemical Engineering Journal, 2025)

Late Quaternary slip rate of the Northern Margin Fault of the Huaizhuo Basin in the North China Block and its seismological implications - Lu-wei Li; Zhong-yuan Yu; Chun-miao Qiu; Wen-xuan Wang; Qian Zhao; Rong-ying Zheng; Yan-Lin Yang (Applied Geophysics, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Active tectonic deformation and its seismic–geological significance of boundary faults of the Daxing Uplift and Langgu–Dachang Depression, Beijing Plain, China - Rong-Ying Zheng; Zhong-Yuan Yu; Bai-Xu Chen; Lu-Wei Li; Yi-Cheng Wang (Applied Geophysics, 2024)

Weakly solvated electrolyte enables the robust solid electrolyte interface on SiOx anodes for lithium-ion battery - Zuojie Xu; Rong Huang; Pengfei Huang; Chaowei He; Shenwen Liu; Haonan Zheng; Wenlong Song; Lu Shi; Weiwei Gao; Dan Li; Hui Huang; Hangjun Ying; et al. (Chemical Engineering Journal, 2024)

Molecularly tailored bifunctional nano-overlayers for efficient and stable inverted perovskite solar cells - Lu-Lu Jiang; Shao-Jie Li; Qi Li; Shuai-Ke Guo; Zhen-Rong Song; Ying-Zhuo Shen; Xiao-Nan Zhang; Dong-Sheng Zheng; Xiao-Dan Tang; Hai-Rui Liu (Chemical Engineering Journal, 2024)

Combined utilization of slag, fly ash, and polyacrylamide for sustainable saline soil improvement: a win-win strategy - Yang Zhao; Zheng Lu; Rong Zhang; Jie Liu; Changtao Hu; Abdollah Tabaroei; Jian Li; Tingzhou Yan; Hailin Yao (Bulletin of Engineering Geology and the Environment, 2024)

A novel hollow flower shaped Cu9S8 antibacterial agent for removing sulfonamide in water environment: effects of composite with magnetic biochar, differential adsorption, and mechanism study - Rui-peng Li; Zheng-rong Hu; Xing Wang; Jun Chen; Qing-qing Liu; Ying Zhao; Zhong-bao Zhao; Xu-lin Lu; Zhi-wei Zhang (Environmental Science and Pollution Research, 2024)

Constructing phonon transport bridges via low-temperature sintering in Diamond@Ag/EP composite to achieve efficient 3D networks structure - Zeyu Zheng; XiaoXin Lu; Liang Xu; Yang Liu; Jianhui Zeng; Hebin Zhang; Jialin Wen; Pengli Zhu; Rong Sun; Weijing Wu (Chemical Engineering Journal, 2024)

MR Molecular Image Guided Treatment of Pancreatic Cancer with Targeted ECO/miR-200c Nanoparticles in Immunocompetent Mouse Tumor Models - Victoria Laney; Ryan Hall; Xueer Yuan; Emma Hampson; Augusta Halle; Grace Yeung; Kristen-Weber Bonk; Suneel Apte; Jordan Winter; Ruth Keri; Zheng-Rong Lu (Pharmaceutical Research, 2024)
Objective Pancreatic ductal adenocarcinoma (PDAC) is characterized by desmoplasia due to increased deposition of extracellular matrix (ECM) proteins. This work investigates the efficacy of targeted ECO/miR-200c nanoparticles (ELNP) on ECM remodeling in PDAC and tumor proliferation with MR molecular imaging (MRMI) with MT218 in immunocompetent mouse models. Methods The miR-200c mediated regulation of EMT markers was measured in PDAC cells in vitro . Wild-type mice bearing mutated KRAS-driven KPC subcutaneous or orthotopic tumors were dosed weekly with RGD-ELNP/miR-200c at 1 mg-RNA/kg for a total of 4 doses. We utilized MT218-MRMI to non-invasively monitor the alteration of tumor ECM EDN-FN levels by miR-200c and tumor response to the treatment. The changes were also validated by posthumous histopathology. Results Transfection of PDAC cells with ELNP/miR-200c downregulated the expression of FN1 and EDB-FN and some mesenchymal markers, inhibiting 3D spheroid formation and migration of KPC PDAC cells. RGD-ELNP/miR-200c treatment resulted in significant signal reduction in the MT218 enhanced MRMI images of both subcutaneous and orthotopic KPC tumors compared to those prior to treatment and treated with a non-specific control. MT218-MRMI results were suggestive of EDB-FN downregulation in tumors, which was later confirmed by immunohistochemistry. Tumor growth in subcutaneous tumors was significantly attenuated with RGD-ELNP/miR-200c and was an observed trend in orthotopic tumors. Substantial necrosis and remodeling were observed in both models treated with RGD-ELNP/miR-200c based on H&E staining. Conclusion These results demonstrate the feasibility of RGD-ELNP/miR-200c in modulating PDAC ECM and restraining tumor growth and the utility of MT218-MRMI for non-invasively monitoring miR-200c efficacy.

In-situ construction of P-doped Ni0.5Cu0.5Co2O4 with 1D/2D hierarchical nanostructure for high-performance hybrid supercapacitors - Rong Zheng; Huiling Lu; Pengjie Zhou; Yulong Ying; Longhua Li; Yu Liu (Chemical Engineering Journal, 2024)

Effects of internal waves on bottom thermal structures and turbulent mixing in the Xisha Islands - Ming-Quan Zhu; Xian-Rong Cen; Sheng-Qi Zhou; Yuan-Zheng Lu; Shuang-Xi Guo; Peng-Qi Huang; Ling Qu (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Correction: Structure and Function of Cationic and Ionizable Lipids for Nucleic Acid Delivery - Da Sun; Zheng-Rong Lu (Pharmaceutical Research, 2024)

Exploring near-bottom turbulent mixing across the Challenger Deep based on temperature spectral analysis - Yuan-Zheng Lu; Shuang-Xi Guo; Sheng-Qi Zhou; Peng-Qi Huang; Jian Lin; Xian-Rong Cen; Ling Qu (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Intravitreal Delivery of PEGylated-ECO Plasmid DNA Nanoparticles for Gene Therapy of Stargardt Disease - Da Sun; Wenyu Sun; Song-Qi Gao; Jonathan Lehrer; Hong Wang; Ryan Hall; Zheng-Rong Lu (Pharmaceutical Research, 2024)

Finite Element Analysis of Percutaneous Anterograde and Retrograde Screws in the Treatment of Superior Rami Pubis Fracture - Hui Lu; Shuo Han; Zheng Lian; Rong Liu; Xuexiao Ma (Journal of Medical and Biological Engineering, 2024)
Purpose This study aims to evaluate the biomechanical characteristics of percutaneous antegrade and retrograde screws in treating superior pubic rami fractures in zone II, employing finite element analysis. It provides a theoretical basis for the treatment of the superior rami of pubis zone II fracture. Methods The software of Mimics and 3-Matic were utilized for reconstructing a fracture model of the superior pubic rami in zone II. Percutaneous screw implantation was simulated for treatment. Material properties were assigned using Mimics, and Ansys software was employed to simulate forces on the S1 vertebral endplate under a 500 N load in a standing posture. Mechanical stability was assessed by comparing these simulations. Results (1) Displacement and stress variations in the pubic bone and screws were consistent across the model and on the fracture site, whether the fracture was in zone I or zone II. However, in zone III, the displacement and stress experienced by the screws were markedly higher than those in zones I and II. (2) When employing an antegrade screw to simulate treatment of a superior pubic rami fracture in zone II, the maximum displacement and stress recorded were 0.88 mm and 15.53 MPa, respectively. Conversely, the use of a retrograde screw for treating a superior pubic rami fracture yielded a maximum displacement of 0.59 mm and stress of 5.51 MPa. Conclusion The biomechanical analysis suggests that for zone II superior pubic rami fractures, where the fracture line is no more than 70 mm from the insertion point (encompassing zones I and II fractures), the use of retrograde screw implantation is preferable.

Epidural administration of large dose of opioid μ receptor agonist may impair cardiac functions and myocardial viability via desensitizing transient receptor potential vanilloid 1 - Xiang Ma; Zheng Guo; Mu-Rong Li; Lu Chen; Xing Zhao; Tian-Qi Wang; Tao Sun (Toxicology and Applied Pharmacology, 2024)

Effect of temperature on fungal nitrification in simulated in-situ aeration of aged MSW landfill - Rong Ye; Weizhong Huo; Xiangyu Zheng; Yuchao Shao; Hongtao Wang; Wenjing Lu (Chemosphere, 2023)

Occurrence of liquid crystal monomers in indoor and outdoor air particle matters (PM10): Implications for human exposure indoors - Li-Li Yao; Jun-Li Wang; Rong-Fa Xu; Ming Zhu; Yan Ma; Bin Tang; Qi-Yuan Lu; Feng-Shan Cai; Xiao Yan; Jing Zheng; Yun-Jiang Yu (Science of The Total Environment, 2023)

Correction: CD142 promotes trophoblast cell migration by inhibiting BCL2-related autophagic degradation of IL-8 - Linmei Zheng; Rong Tang; Lei Shi; Zhongyi Zhou; Jie Song; Zhicheng Lu (In Vitro Cellular & Developmental Biology - Animal, 2023)

Climatic aridification restrained late Cenozoic denudation of the Tian Shan in the inland of Asia - Yutong Jiang; Honghua Lu; Ruohong Jiao; Lichen Pang; Rong Yang; Menghan Wu; Xiangmin Zheng; Youli Li (Global and Planetary Change, 2023)

Linear relationship between CH4 fluxes and atmospheric CO2 concentration levels controlled by rice biomass and soil methanogenic communities - Yuanyuan Wang; Zhenghua Hu; Shuqi He; Qiang Jing; Lidong Shen; Chao Liu; Zhurong Wu; Wei Huang; Guihua Lu; Rui Cao; Kezhi Zheng; Ning Dong; et al. (Nutrient Cycling in Agroecosystems, 2023)

Experimental investigation of the seismic resistance of RC beam–column connections after freeze–thaw cycle treatment - Xian-Liang Rong; Lei Li; Wei-Yuan Huang; Li-Guo Dong; Shan-Suo Zheng; Feng Wang; Dong Lu; Jun-Yan Wang (Engineering Structures, 2023)

Detection of spatiotemporal changes in ecological quality in the Chinese mainland: Trends and attributes - Yang Li; Haifeng Tian; Jingfei Zhang; Siqi Lu; Zhixiang Xie; Wei Shen; Zhicheng Zheng; Mengdi Li; Peijun Rong; Yaochen Qin (Science of The Total Environment, 2023)

Achieving high yield and nitrogen agronomic efficiency by coupling wheat varieties with soil fertility - Keyu Ren; Minggang Xu; Rong Li; Lei Zheng; Huiying Wang; Shaogui Liu; Wenju Zhang; Yinghua Duan; Changai Lu (Science of The Total Environment, 2023)

SRSF1 is crucial for male meiosis through alternative splicing during homologous pairing and synapsis in mice - Longjie Sun; Juan Chen; Rong Ye; Zheng Lv; Xuexue Chen; Xiaomei Xie; Yuheng Li; Chaofan Wang; Pengbo Lv; Lu Yan; Shuang Tian; Xiaohong Yao; et al. (Science Bulletin, 2023)

Rare earth elements detoxification mechanism in the hyperaccumulator Dicranopteris linearis: [silicon-pectin] matrix fixation - Hong-Xiang Zheng; Yu-Lu Yang; Wen-Shen Liu; Ying Zhong; Yue Cao; Rong-Liang Qiu; Chong Liu; Antony van der Ent; Martin J. Hodson; Ye-Tao Tang (Journal of Hazardous Materials, 2023)

Effect of shape-stable phase change materials on heat transfer characteristics of ground source heat pump backfill materials - Rong Wan; Lu Shen; Hengjun Liu; Songfeng Ma; Shangwen Duan; Dequan Kong; Ting Wang; Chen Zheng (Geothermics, 2023)

Nonlinear gas-spring DVA for seismic response control: Experiment and numerical simulation - Kunjie Rong; Zheng Lu; Jiawei Zhang; Mengyao Zhou; Weiyuan Huang (Engineering Structures, 2023)

Anti-inflammatory flavonoid derivatives from the heartwood of Dalbergia odorifera T. Chen - Ni-li Zan; Zi-Han Lu; Xin-Yu Wang; Rong-Ye Wang; Nai-Yun Liang; Hui-Xia Huo; Yun-Fang Zhao; Yue-Lin Song; Peng-Fei Tu; Jiao Zheng; Jun Li (Natural Product Research, 2023)

A 40 % paddy surface soil organic carbon increase after 5-year no-tillage is linked with shifts in soil bacterial composition and functions - Jian-Ying Qi; Xiang-Bin Yao; Jian Lu; Long-Xin He; Jun-Li Cao; Zheng-Rong Kan; Xing Wang; Sheng-Gang Pan; Xiang-Ru Tang (Science of The Total Environment, 2023)

RETRACTED ARTICLE: CD142 promotes trophoblast cell migration by inhibiting BCL2-related autophagic degradation of IL-8 - Linmei Zheng; Rong Tang; Lei Shi; Zhongyi Zhou; Jie Song; Zhicheng Lu (In Vitro Cellular & Developmental Biology - Animal, 2023)

Nucleic Acid Delivery - Zheng-Rong Lu; Galen H. Shi (Pharmaceutical Research, 2023)

Structure and Function of Cationic and Ionizable Lipids for Nucleic Acid Delivery - Da Sun; Zheng-Rong Lu (Pharmaceutical Research, 2023)

A low-cost in-situ CO2 sensor based on a membrane and NDIR for long-term measurement in seawater - Meng Li; Baolu Du; Jinjia Guo; Zhihao Zhang; Zeyu Lu; Rong’er Zheng (Journal of Oceanology and Limnology, 2022)

Predictive value of monocyte to HDL cholesterol ratio for stroke-associated pneumonia in patients with acute ischemic stroke - Yaming Sun; Juan Lu; Danni Zheng; Jufen Qian; Hongxin Zhang; Dong Xing; Fengdan Rong; Yongjun Cao; Chun-Feng Liu; Shoujiang You (Acta Neurologica Belgica, 2021)

The effect of the PARK16 rs11240572 variant on brain structure in Parkinson's disease - Lu-yan Gu; Shao-bing Dai; Cheng Zhou; Ting Gao; Jing-jing Wu; Yi Fang; Xiao-jun Guan; Tao Guo; Ran Zheng; Chongyao Jin; Xiao-jun Xu; Zhe Song; et al. (Brain Structure and Function, 2021)

Efficacy of Targeted ECO/miR-200c Nanoparticles for Modulating Tumor Microenvironment and Treating Triple Negative Breast Cancer as Non-invasively Monitored by MR Molecular Imaging - Andrew L. Schilb; Nadia R. Ayat; Amita M. Vaidya; Laura M. Hertz; Ryan C. Hall; Josef H. Scheidt; Da Sun; Zhanhu Sun; Ramamurthy Gopalakrishnan; Zheng-Rong Lu (Pharmaceutical Research, 2021)

Induction of thoracic aortic dissection: a mini-review of β-aminopropionitrile-related mouse models - Hai-qiong Zheng; Jia-bing Rong; Fei-ming Ye; Yin-chuan Xu; Hong S. Lu; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2020)

Comparative transcriptome analysis reveals a gene expression profile that contributes to rhizome swelling in Panax japonicus var. major - Jun Rong Tang; Ying Chun Lu; Zheng Jie Gao; Wan Ling Song; Kun Hua Wei; Yan Zhao; Qing Yan Tang; Xue Jiao Li; Jun Wen Chen; Guang Hui Zhang; Guang Qiang Long; Wei Fan; et al. (Plant Biosystems, 2020)

Release from below- and aboveground natural enemies contributes to invasion success of a temperate invader - Yuan-Zheng Zhao; Ming-Chao Liu; Yu-Long Feng; Dong Wang; Wei-Wei Feng; Keith Clay; Lekeah A. Durden; Xiu-Rong Lu; Shuo Wang; Xiao-Lin Wei; De-Liang Kong (Plant and Soil, 2020)

Antifungal xanthones produced by the endophytic fungus Paraconionthyrium sp. YM 311593 - Cuiping Miao; Junfei Wang; Rong Huang; Sisi Liu; Kaixuan Zheng; Chuansheng Liu; Yihan Lu; Shaohua Wu (Folia Microbiologica, 2020)

Influence of Aphis gossypii feeding on defense strategy of native and introduced populations of Ageratina adenophora - Ying Lin; Shu-Qi He; Zhi-Hui Lu; Yu-Lin Gao; Yan-Ru Duan; Zheng-Yue Li; Bin Chen; Fu-Rong Gui (Arthropod-Plant Interactions, 2020)

Developing stripe rust resistant wheat (Triticum aestivum L.) lines with gene pyramiding strategy and marker-assisted selection - Rong Liu; Jing Lu; Min Zhou; Shigang Zheng; Zehou Liu; Chihong Zhang; Mei Du; Minxiu Wang; Yunfang Li; Yu Wu; Lei Zhang (Genetic Resources and Crop Evolution, 2020)

Characterization and diagnostic marker development for Yr28-rga1 conferring stripe rust resistance in wheat - Shigang Zheng; Yu Wu; Min Zhou; Lian Zeng; Rong Liu; Yunfang Li; Zehou Liu; Chihong Zhang; Lu Lu; Lei Zhang (European Journal of Plant Pathology, 2020)

DNA methylation levels in different tissues in tea plant via an optimized HPLC method - Ying Gao; Jia-Li Hao; Zhen Wang; Kwan-Jeong Song; Jian-Hui Ye; Xin-Qiang Zheng; Yue-Rong Liang; Jian-Liang Lu (Horticulture, Environment, and Biotechnology, 2019)

Polymorphisms in the APOBEC3G gene of Chinese rhesus macaques affect resistance to ubiquitination and degradation mediated by HIV-2 Vif - Zhi-Qiang Jiang; Xu-Rong Yao; Hang Yu; Yue-Er Lu; Bei-Lei Liu; Feng-Liang Liu; Ya-Bin Jin; Min Zhuo; Yong-Tang Zheng; Fei Ling (Archives of Virology, 2019)

Two new benzophenones and one new natural amide alkaloid isolated from a mangrove-derived Fungus Penicillium citrinum - Cai-Juan Zheng; Hai-Xia Liao; Rong-Qing Mei; Guo-Lei Huang; Lu-Jia Yang; Xue-Ming Zhou; Tai-Ming Shao; Guang-Ying Chen; Chang-Yun Wang (Natural Product Research, 2019)

In Vitro Susceptibility of Berberine Combined with Antifungal Agents Against the Yeast Form of Talaromyces marneffei - Hong Luo; Kai-su Pan; Xiao-lu Luo; Dong-yan Zheng; Alex Andrianopoulos; Le-min Wen; Yan-qing Zheng; Jing Guo; Chun-yang Huang; Xiu-ying Li; Rong Hu; Yu-jiao Li; et al. (Mycopathologia, 2019)

Comparative analysis of root transcriptome profiles between low- and high-cadmium-accumulating genotypes of wheat in response to cadmium stress - Min Zhou; Shigang Zheng; Rong Liu; Jing Lu; Lu Lu; Chihong Zhang; Zehou Liu; Congpei Luo; Lei Zhang; Yu Wu (Functional & Integrative Genomics, 2019)

Neuroinflammation in acute hepatic encephalopathy rats: imaging and therapeutic effectiveness evaluation using 11C-PK11195 and 18F-DPA-714 micro-positron emission tomography - Song Luo; Xiang Kong; Jin Rong Wu; Chun Yan Wang; Ying Tian; Gang Zheng; Yun Yan Su; Guang Ming Lu; Long Jiang Zhang; Gui Fen Yang (Metabolic Brain Disease, 2018)

Protective effect of the total flavonoids from Apocynum venetum L. on carbon tetrachloride-induced hepatotoxicity in vitro and in vivo - Wei Zhang; Zheng Dong; Xiujuan Chang; Cuihong Zhang; Guanghua Rong; Xudong Gao; Zhen Zeng; Chunping Wang; Yan Chen; Yihui Rong; Jianhui Qu; Ze Liu; et al. (Journal of Physiology and Biochemistry, 2018)

Correction to: Risk exposure assessment of per- and polyfluoroalkyl substances (PFASs) in drinking water and atmosphere in central eastern China - Zhibo Lu; Rong Lu; Hongyuan Zheng; Jing Yan; Luning Song; Juan Wang; Haizhen Yang; Minghong Cai (Environmental Science and Pollution Research, 2018)

Risk exposure assessment of per- and polyfluoroalkyl substances (PFASs) in drinking water and atmosphere in central eastern China - Zhibo Lu; Rong Lu; Hongyuan Zheng; Jing Yan; Luning Song; Juan Wang; Haizhen Yang; Minghong Cai (Environmental Science and Pollution Research, 2018)

Lipid accumulation and anti-rotifer robustness of microalgal strains isolated from Eastern China - Cheng Yuan; Yan-Lin Zheng; Wan-Lu Zhang; Ru He; Yong Fan; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2017)

Lower functional connectivity of default mode network in cognitively normal young adults with mutation of APP, presenilins and APOE ε4 - Yun Yan Su; Xiao Dong Zhang; U. Joseph Schoepf; Akos Varga-Szemes; Andrew Stubenrauch; Xue Liang; Li Juan Zheng; Gang Zheng; Xiang Kong; Qiang Xu; Shou Ju Wang; Rong Feng Qi; et al. (Brain Imaging and Behavior, 2017)

Evaluating the contribution of Yr genes to stripe rust resistance breeding through marker-assisted detection in wheat - Shigang Zheng; Yunfang Li; Lu Lu; Zehou Liu; Chihong Zhang; Donghui Ao; Lirong Li; Chunyan Zhang; Rong Liu; Congpei Luo; Yu Wu; Lei Zhang (Euphytica, 2017)

Using PG-Liposome-Based System to Enhance Puerarin Liver-Targeted Therapy for Alcohol-Induced Liver Disease - Ying-Zheng Zhao; Lu Zhang; Pardeep K. Gupta; Fu-Rong Tian; Kai-Li Mao; Kai-Yan Qiu; Wei Yang; Chuan-Zhu Lv; Cui-Tao Lu (AAPS PharmSciTech, 2016)

The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Degradation and detoxification of the triphenylmethane dye malachite green catalyzed by crude manganese peroxidase from Irpex lacteus F17 - Xueting Yang; Jinzhao Zheng; Yongming Lu; Rong Jia (Environmental Science and Pollution Research, 2016)

Anti-angiogenic Effects of Bumetanide Revealed by DCE-MRI with a Biodegradable Macromolecular Contrast Agent in a Colon Cancer Model - Anthony S. Malamas; Erlei Jin; Qi Zhang; John Haaga; Zheng-Rong Lu (Pharmaceutical Research, 2015)

The E23K and A190A variations of the KCNJ11 gene are associated with early-onset type 2 diabetes and blood pressure in the Chinese population - Langen Zhuang; Yu Zhao; Weijing Zhao; Ming Li; Ming Yu; Ming Lu; Rong Zhang; Xiaoxu Ge; Taishan Zheng; Can Li; Jun Yin; Jingyuan Yin; et al. (Molecular and Cellular Biochemistry, 2015)

The mechanism of UVB irradiation induced-apoptosis in cataract - Yinghong Ji; Lei Cai; Tianyu Zheng; Hongfei Ye; Xianfang Rong; Jun Rao; Yi Lu (Molecular and Cellular Biochemistry, 2015)

Hepatocellular Carcinoma in Budd-Chiari Syndrome: Enhancement Patterns at Dynamic Gadolinium-Enhanced T1-Weighted MR Imaging - Chun Yang; Kai Xu; Junnian Zheng; Ping Ma; Chunfeng Hu; Shaodong Li; Yutao Rong; Xin Lu; Qingqiao Zhang; Maoheng Zu; Rong Hua; Ling Zhang (Cell Biochemistry and Biophysics, 2014)

Theranostics: Fusion of Therapeutics and Diagnostics - Zheng-Rong Lu (Pharmaceutical Research, 2014)

Synthesis and Evaluation of a Targeted Nanoglobular Dual-Modal Imaging Agent for MR Imaging and Image-Guided Surgery of Prostate Cancer - Mingqian Tan; Zhen Ye; Daniel Lindner; Susann M. Brady-Kalnay; Zheng-Rong Lu (Pharmaceutical Research, 2014)

The Leu72Met polymorphism of the GHRL gene prevents the development of diabetic nephropathy in Chinese patients with type 2 diabetes mellitus - Langen Zhuang; Ming Li; Changhua Yu; Can Li; Mingming Zhao; Ming Lu; Taishan Zheng; Rong Zhang; Weijing Zhao; Yuqian Bao; Kunsan Xiang; Weiping Jia; et al. (Molecular and Cellular Biochemistry, 2014)

Transjugular intrahepatic portosystemic shunt induced short- and long-term cerebral blood flow variations in cirrhotic patients: an arterial spin labeling MRI study - Gang Zheng; Long Jiang Zhang; Yue Cao; Zhiying Pan; Rong Feng Qi; Ling Ni; Donghong Shi; Xinxin Fan; Guang Ming Lu (Metabolic Brain Disease, 2013)

Physical characteristics of Chinese Hakka - LianBin Zheng; YongLan Li; ShunHua Lu; JinPing Bao; Yang Wang; XiaoRui Zhang; Hong Xue; WenGuo Rong (Science China Life Sciences, 2013)

Enhancing production of a 24-membered ring macrolide compound by a marine bacterium using response surface methodology - Hua Chen; Mian-bin Wu; Zheng-jie Chen; Ming-lu Wang; Jian-ping Lin; Li-rong Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Association of interleukin-1 gene polymorphisms with multiple sclerosis: a meta-analysis - Jian Huang; Zi-Kang Xie; Rong-Bin Lu; Zheng-Fu Xie (Inflammation Research, 2013)

MR Molecular Imaging of Prostate Cancer with a Peptide-Targeted Contrast Agent in a Mouse Orthotopic Prostate Cancer Model - Mingqian Tan; Susan M. Burden-Gulley; Wen Li; Xueming Wu; Daniel Lindner; Susann M. Brady-Kalnay; Vikas Gulani; Zheng-Rong Lu (Pharmaceutical Research, 2012)

Ocular Pharmacokinetic Study Using T1 Mapping and Gd-Chelate- Labeled Polymers - Xianfeng Shi; Xin Liu; Xueming Wu; Zheng-Rong Lu; S. Kevin Li; Eun-Kee Jeong (Pharmaceutical Research, 2011)

Single nucleotide polymorphism of CACNA2D1 gene and its association with milk somatic cell score in cattle - Zheng Rong Yuan; Jiao Li; Li Liu; Lu Pei Zhang; Li Min Zhang; Cui Chen; Xiao Jie Chen; Xue Gao; Jun Ya Li; Jin Bao Chen; Hui Jiang Gao; Shang Zhong Xu (Molecular Biology Reports, 2011)

Expression, purification, and activity assay of peptide deformylase from Escherichia coli and Staphylococcus aureus - Xuchun Che; Jinwei Hu; Lijuan Wang; Zhifeng Zhu; Qiong Xu; Junqiang Lv; Zheng Fu; Yajun Sun; Jia Sun; Gang Lin; Rong Lu; Zhi Yao (Molecular and Cellular Biochemistry, 2011)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

Effect of dietary fatty acids on serum parameters, fatty acid compositions, and liver histology in Shaoxing laying ducks - Wei-meng Liu; Shu-jing Lai; Li-zhi Lu; Fang-xiong Shi; Jing Zhang; Yu Liu; Bo Yu; Zheng-rong Tao; Jun-da Shen; Guo-qin Li; De-qian Wang; Jin-jun Li; et al. (Journal of Zhejiang University-SCIENCE B, 2011)

Increased urinary 8-hydroxy-2′-deoxyguanosine levels in workers exposed to di-(2-ethylhexyl) phthalate in a waste plastic recycling site in China - Qian Wang; Li Wang; Xi Chen; Kai Min Rao; Shao You Lu; Sheng Tao Ma; Pu Jiang; Dan Zheng; Shun Qing Xu; Hong Yan Zheng; Jian Shu Wang; Zhi Qiang Yu; et al. (Environmental Science and Pollution Research, 2011)

Methotrexate ameliorates pristane-induced arthritis by decreasing IFN-γ and IL-17A expressions - Wei-kun Hou; Lie-su Meng; Fang Zheng; Yu-rong Wen; Wen-hua Zhu; Cong-shan Jiang; Xiao-jing He; Yan Zhou; She-min Lu (Journal of Zhejiang University-SCIENCE B, 2011)

Stability and Biodistribution of a Biodegradable Macromolecular MRI Contrast Agent Gd-DTPA Cystamine Copolymers (GDCC) in Rats - Xueming Wu; Yuda Zong; Zhen Ye; Zheng-Rong Lu (Pharmaceutical Research, 2010)

Tumor Characterization with Dynamic Contrast Enhanced Magnetic Resonance Imaging and Biodegradable Macromolecular Contrast Agents in Mice - Xueming Wu; Yi Feng; Eun-Kee Jeong; Lyska Emerson; Zheng-Rong Lu (Pharmaceutical Research, 2009)

Systematic biotic responses to palaeoenvironmental change in the Late Pleistocene southern South China Sea: a preliminary study - Muhong Chen; Qianyu Li; Lanlan Zhang; Fan Zheng; Jun Lu; Rong Xiang; Lili Zhang; Wen Yan; Zhong Chen; Shangbin Xiao (Journal of Quaternary Science, 2008)
Oxygen and carbon isotopes from the planktonic foraminifer Globigerinoides sacculifer , trace element contents, calcium carbonate, biogenic silica, grain size, and abundances of diatoms, radiolarians and foraminifera in a deep‐sea core from the southwestern South China Sea were analysed to investigate the response of various marine ecological communities to environmental changes over the last 200 ka. The synthesised results show that the quality of the palaeoecological environment for biological growth is primarily affected by nutrient supply and terrigenous disturbance. Ba and P are important nutrient elements for the growth of diatoms, radiolarians and planktonic foraminifera. Together with dissolved silica and calcium carbonate in sea water, these elements may control microbiotic development. However, variations in Fe content appear to affect diatom and radiolarian abundance. Optimal biotic growth occurs when nutrients are abundant and when there is minimal terrigenous disturbance. Biotic growth decreases when sea water is highly oligotrophic and terrigenous input is high. Maximum biological growth occurred in the mid Holocene, but deteriorated soon afterwards owing to increased terrigenous input, causing a decrease of biological abundance and productivity in the late Holocene. The results also indicate how the Toba volcanic eruption ca. 74 ka ago contributed to changing the ecological environment in the southern South China Sea. Copyright © 2008 John Wiley & Sons, Ltd.

Contrast-Enhanced MRI-Guided Photodynamic Cancer Therapy with a Pegylated Bifunctional Polymer Conjugate - Anagha Vaidya; Yongen Sun; Yi Feng; Lyska Emerson; Eun-Kee Jeong; Zheng-Rong Lu (Pharmaceutical Research, 2008)

Noninvasive Visualization of Pharmacokinetics, Biodistribution and Tumor Targeting of Poly[N-(2-hydroxypropyl)methacrylamide] in Mice Using Contrast Enhanced MRI - Yanli Wang; Furong Ye; Eun-Kee Jeong; Yongen Sun; Dennis L. Parker; Zheng-Rong Lu (Pharmaceutical Research, 2007)

Application of Biomedical Imaging in Drug Discovery and Development - Zheng-Rong Lu (Pharmaceutical Research, 2007)

Assignment of CCR7 gene to chicken chromosome 27 by radiation hybrid panel mapping - Yong Tian; Li-zhi Lu; Yan Fu; Zheng-rong Tao; Jun-da Shen; De-qian Wang; Ai-ping Yuan; Zhao-zheng Yin (Journal of Zhejiang University-SCIENCE B, 2007)

Pharmacokinetics, Biodistribution and Contrast Enhanced MR Blood Pool Imaging of Gd-DTPA Cystine Copolymers and Gd-DTPA Cystine Diethyl Ester Copolymers in a Rat Model - Yi Feng; Yuda Zong; Tianyi Ke; Eun-Kee Jeong; Dennis L. Parker; Zheng-Rong Lu (Pharmaceutical Research, 2006)

Gd-DTPA l-Cystine Bisamide Copolymers as Novel Biodegradable Macromolecular Contrast Agents for MR Blood Pool Imaging - Todd L. Kaneshiro; Tianyi Ke; Eun-Kee Jeong; Dennis L. Parker; Zheng-Rong Lu (Pharmaceutical Research, 2006)

Pharmacokinetics and Tissue Retention of (Gd-DTPA)-Cystamine Copolymers, a Biodegradable Macromolecular Magnetic Resonance Imaging Contrast Agent - Xinghe Wang; Yi Feng; Tianyi Ke; Matthias Schabel; Zheng-Rong Lu (Pharmaceutical Research, 2005)

Direct plantlet regeneration from the tuber of Stachys sieboldii - Wei Li; Huan-Huan Gao; Rong Lu; Guang-Qing Guo; Guo-Chang Zheng (Plant Cell, Tissue and Organ Culture (PCTOC), 2002)

Mapping of leaf and neck blast resistance genes with resistance gene analog, RAPD and RFLP in rice - Jie-Yun Zhuang; Wen-Bin Ma; Jian-Li Wu; Rong-Yao Chai; Jun Lu; Ye-Yang Fan; Min-Zhong Jin; Hei Leung; Kang-Le Zheng (Euphytica, 2002)

Targeted Delivery of Doxorubicin by HPMA Copolymer-Hyaluronan Bioconjugates - Yi Luo; Nicole J. Bernshaw; Zheng-Rong Lu; Jindrich Kopecek; Glenn D. Prestwich (Pharmaceutical Research, 2002)

Influence of the Structure of Drug Moieties on the in Vitro Efficacy of HPMA Copolymer–Geldanamycin Derivative Conjugates - Yuji Kasuya; Zheng-Rong Lu; Pavla Kopečková; S. Esmail Tabibi; Jindřich Kopeček (Pharmaceutical Research, 2002)